Risks, threats and mechanisms of management systems ESG-transformation - A. M. Margolin; I. V. Vyakina (Модернизация, инновация, развитие)
Purpose: the article aims at justification and identification of the factors hindering the effective implementation of the management systems ESG-transformation, taking into account new risks and threats to sustainable development, and substantiation of the mechanisms that ensure its implementation.Methods: along with the traditional methods of scientific analysis, interdisciplinary approach typical for the study of sustainable development problems and the diagnosis of key factors associated with ESG-transformation of management systems, carried out a review of scientific literature, used various rating models, regulatory documents and guidelines for sustainable development, corporate social responsibility and diagnostics of ESG-factors.Results: the article performed diagnostics of managed and unmanaged risks of ESG-transformation of management systems, identified trends in the development of managerial personnel competencies that carry out such a transformation, and disclosed the features of achieving sustainable development goals. The essence of the author's position is that in order to achieve any of the sustainable development goals, two mandatory conditions must be met: ensuring effective interaction between the state, business and civil society and applying an integrated approach to considering economic, social and environmental aspects that reflect its specifics.Сonclusions and Relevance: the proposed approach makes it possible to develop scientifically based tools for minimizing risks and mechanisms for achieving sustainable development goals based on the ESG-transformation of management systems. Results obtained in the article may be useful for the professional community interested in promoting the ESG-agenda and achieving sustainable development goals based on the ESG-transformation of public and corporate governance.